Ambiente de Aprendizaje Virtual: una oportunidad para la construcción de la Cátedra de la Paz (2021)
This work seeks to create teaching material that would allow students and teachers to approach the subject of peace and its contents, specifically historical memory and conflict resolution. In order to achieve this approach and learning in general, the construction of a virtual learning environment is proposed as an educational resource that supports and backs up the teaching-learning process related to the thematic axes of the peace chair.